PENGARUH PENGALAMAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA CV. LAPAN LAPAN JAYA ABADI DI MEDAN - Nurjannah, Nurjannah; Nasution, Umar Hamdan; Zulkarnain, Mierna (Bisnis-Net, 2025)
Human Resources are an important element in an organization or company, so that management activities run well. Employee performance cannot be separated from the employee's work experience factor, because the more experience they have, the faster they will be able to work. In addition to work experience, factors that can influence employee performance are also found in the leadership style factor in leading a company.The purpose of this study was to determine the effect of work experience and leadership style on employee performance. The method in this study used a quantitative research method, with a sample of 48 respondents who were all employees of CV. Lapan - Lapan Jaya Abadi Medan, with data analysis techniques using the SPSS Version 25 application. The results of the study showed that the results of the t-count statistical test were 3.969 and the t-table value was 1.67866, this means that t count> t table or 3.969> 1.67866, indicating that leadership style gets a significance value of 0.000, the result of the significance value is less than 0.05. Thus Ha is accepted, which means that leadership style has an effect on employee performance. So it can be proven that hypothesis 1 is accepted and it can be concluded that leadership style has a positive and significant effect on employee performance. The results of the statistical test t count of 3.209 and the value of t table of 1.67866, this means that t count> t table or 3.209> 1.67866, indicating that work experience gets a significance value of 0.001, the result of the significance value is smaller than 0.05. Thus Ha is accepted which means that work experience has an effect on employee performance. So it can be proven that hypothesis 1 is accepted and it can be concluded that work experience has a positive and significant effect on employee performance. The value of F count 15.336 with the value of F table then it is said 15.336> 3.20 with F sig. 0.000 where F sig. 0.000 is smaller than 0.05 then Ho is rejected. It can be interpreted that simultaneously work experience (X1) and leadership style (X2), have a significant effect on employee performance (Y).